Environmental Noise Pollution and Impact in Major Markets of Akwa Ibom State, Nigeria (Global Journal of Human-Social Science, 2018)
Environmental noise pollution and impact in some markets of Akwa Ibom State, Nigeria have been carried out. The average maximum noise level of 90.4 dB(A), 85.2 dB(A) and 74.3dB(A), recorded in the mornings, afternoons and evenings constitute a health hazard for the vendors and buyers in these markets as they exceed the recommended standards. The average minimum values of 66.66, 63.7 and 60.0dB(A) were also recorded for mornings, afternoons and evenings. Reduced hearing acuity, speech intelligibility and clarity, communication disturbances and fatigue were some of the negative impacts on the market operators as acknowledged during the subjective assessment of the respondents. Lock-up shops which should serve as noise barriers should be provided in these market to replace the open market operations as this would reduce the emitted noise and the negative impacts.
Keywords: environmental noise pollution; noise levels; hearing acuity; speech intelligibility and clarity; fatigue; communication